The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fneur.2017.00249
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Temporal Coupling of Tactile Perception and Motor Action in Parkinson’s Disease

Abstract: Evidence shows altered somatosensory temporal discrimination threshold (STDT) in Parkinson’s disease in comparison to normal subjects. In healthy subjects, movement execution modulates STDT values through mechanisms of sensory gating. We investigated whether STDT modulation during movement execution in patients with Parkinson’s disease differs from that in healthy subjects. In 24 patients with Parkinson’s disease and 20 healthy subjects, we tested STDT at baseline and during index finger abductions (at movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
0
20
1
Order By: Relevance
“…However, the direction of the changes in PD is opposite to the direction we observed in dystonia. In PD there is reduced modulation of STDT associated with slowing of movement execution during sensorimotor integration, whereas in our study we observed that movement velocity in patients with CD and FHD did not vary during the sensorimotor integration task.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…However, the direction of the changes in PD is opposite to the direction we observed in dystonia. In PD there is reduced modulation of STDT associated with slowing of movement execution during sensorimotor integration, whereas in our study we observed that movement velocity in patients with CD and FHD did not vary during the sensorimotor integration task.…”
Section: Discussioncontrasting
confidence: 90%
“…Abnormal modulation of the STDT during voluntary movement is also present in patients with Parkinson's disease (PD) . However, the direction of the changes in PD is opposite to the direction we observed in dystonia.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…For this reason, it is considered that an abnormal TDT is a marker of defective inhibition within the superior colliculus or arising from substantia nigra pars compacta ( 34 ). Further strengthening the idea that these subcortical structures integrate temporal information comes from the altered TDT values reported in patients with various basal ganglia disorders ( 1 , 35 39 ).…”
Section: The Neuroanatomy Of Temporal Discriminationmentioning
confidence: 59%
“…The STDT was investigated according to the experimental procedures used in previous studies [15,[37][38][39][40][41]. Paired tactile stimuli for STDT testing consisted of square-wave electrical pulses delivered by means of a constant current stimulator (Digitimer DS7AH) through surface electrodes over the distal phalanx of the right index finger.…”
Section: Stdt Testingmentioning
confidence: 99%